Legal Power of Electronic Evidence in Proving Criminal Cases Based on the 2023 Criminal Code - Dwiki Pernandes Sembiring; Kartina Pakpahan; Elvira Fitriyani Pakpahan (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
E-commerce is a trade transaction that allows buying and selling without having to meet directly between the seller and the buyer. This trading system requires a strong sense of trust between one another, between the seller and the buyer. Recognition of electronic evidence as evidence that can be submitted to court and recognized as valid as evidence, has been carried out since 1977 through the Company Documents Law which stipulates that microfilm containing a recording of a company's documents can be submitted as evidence in court if a lawsuit arises later. According to the Company Documents Law, electronic document evidence is part of written evidence, while the Corruption Law explicitly explains that electronic information and electronic documents are an extension of indicative evidence. Because electronic mail in the form of electronic information or electronic documents has been recognized as one of the valid evidence in special crimes outside the Criminal Code in line with valid evidence in Article 184 of the Criminal Procedure Code is a new type of evidence, it is hoped that investigators, prosecutors, legal advisors and judges have an understanding of this electronic evidence. In the examination of criminal cases, it is expected that the judge in imposing a sentence based on two valid pieces of evidence and the judge obtains the conviction that the defendant is guilty of committing a crime, then the judge must impose the maximum sentence according to the prosecutor's demands, so that the defendant is deterred and the sense of justice of the community is fulfilled.